Investigation of an Induction Wound Rotor Motor to Work as a Synchronous Generator - Al-Rawashdeh, A. Y. (Engineering, Technology & Applied Science Research, 2019)
This paper aims at investigating the use of an induction wound rotor motor to generate voltage instead of the old diesel engines that are still used in many factories, like old cement factories, in Jordan. In this investigation, a simulation model of induction wound rotor motor was implemented using Matlab/Simulink. The excitation dc current was connected to a two-phase rotor circuit, and the voltage-current performance characteristics were investigated and evaluated under different load types. The simulation results confirmed the possibility of using the induction wound rotor motor as a synchronous generator.